Surface controlled generation of reactive radicals from persulfate by carbocatalysis on nanodiamonds - Duan, Xiaoguang; Su, Chao; Zhou, Li; Sun, Hongqi; Suvorova, A.; Odedairo, T.; Zhu, Z.; Shao, Zongping; Wang, Shaobin (Elsevier BV, 2016)
Production of radicals by metal-free catalysis is expected to offer a promising oxidative reaction for remediation of emerging contaminants. In this study, novel metal-free activation of persulfate (PS) on annealed nanodiamonds (ANDs) was investigated, which demonstrated superior performances in decomposition of various pollutants to conventional metal-based catalysis. Comprehensive investigations on the effects of reaction parameters, such as solution pH, reaction temperature, initial phenol concentration, catalyst loading, PS usage, the presence of chlorine ions and humic acid, on phenol degradation were carried out. In addition, nanodiamond (ND) material optimization and reusability were also studied. Electron paramagnetic resonance (EPR) and selective organic degradation unraveled that the PS/AND system may produce both hydroxyl radicals (·OH) and sulfate radicals (SO4 · -), initialized from oxidizing water molecules on the nanodiamond surface. The carbocatalysts served as an excellent electron tunnel to facilitate the charge transfer from water or hydroxide ions to PS, and the oxidized intermediates may play a crucial role in PS activation. Electrochemical analyses in PS oxidant solution and oxygen reduction reaction (ORR) were carried out to understand OO bond activation by the metal-free catalysis. This study provides an environmentally benign and highly efficient oxidative reaction system with reactive radicals along with insights into the metal-free PS activation process.